Physiological Process of Acacia mangium Willd. Plant of Six Months Old Attacked by Black Spots Disease in PT Itci Hutani Manunggal Terunen - Helda Syahfari; Ach. Arieffin Bratawinata; Maman Sutisna; Djumali Mardji (International Journal of Science and Engineering, 2013)
The purposes of this study were to determine symptoms and signs of black spot disease on mangium plants of 6 months old, frequency of the attacks and their effects on physiological processes of affected phyllode (amount of chlorophyll, transpiration, evaporation and water potential of phyllode). Fieldwork was conducted in the research plots measuring 25 m x 25 m) in mangium plantation. Observed plants were 6 months old amounted to 104 plants at a spacing of 3 m x 2 m, the seedlings were originated from Riau Islands. Plants were observed in the census in research plots .The results showed that the black spot disease was caused by a fungus Meliola brisbanensis with symptoms of black spots on phyllode, where the spots occured more on the upper surface than the lower surface. Other than phyllode, young part of the stem was also attacked. Attacked phyllode changed in color from green to yellow (chlorotic). Frequency of attacks on plot of 6 months old was 62.5%. The amount of chlorophyll in phyllode attacked by black spot fungus was 40.8 Spad. Transpiration velocity had the value of 1284.26 gr/dm2/second, evaporation rate of 0.00019 μgcm2/minute. Water potential of phyllode at 08:00 to 10:00 a.m was 18 bars, at 12:00 a.m to 14:00 p.m 21.2 bars and at 4:00 p.m. to 6:00 p.m. was 9 bars. Environmental factors that influence the physiological process of black spot fungus were soil pH, irradiation intensity, water content of soil and were influenced by factors inside of the black spot disease itself. Doi: 10.12777/ijse.5.1.15-18 [How to cite this article: Syahfari, H., Bratawinata, A.A., Sutisna, M. and Mardji, D. (2013). Physiological Process of Acacia mangium Willd. Plant of Six Months Old Attacked by Black Spots Disease in PT ITCI Hutani Manunggal Terunen. International Journal of Science and Engineering, 5(1),6-11. Doi: 10.12777/ijse.5.1.15-18 ]